Model Evaluasi CIPP dalam Menilai Efektivitas Program BK di SMP Berbasis Islam - Murwanto Setyo Nugroho; Erda Farid Hidayani; Itang Enrico Pradana Mahardhika; Ahmad Muhibbin; Dwi Setyo Astuti (Educatio, 2026)
This study aims to evaluate the effectiveness of the Guidance and Counseling (GC) program at Islamic-based junior high schools using the CIPP evaluation model (Context, Input, Process, Product). A descriptive-evaluative method was employed, with data collected through questionnaires, interviews, observations, and document analysis. The participants included 109 students, a school counselor, the principal, subject teachers, and parents, selected purposively. Findings indicate that the context component received the highest score (3.9), reflecting strong alignment between the program and students’ needs. The product component scored 3.5, suggesting a positive impact on student behavior, learning motivation, and psychological well-being. These outcomes are illustrated through a bar chart highlighting each aspect of the CIPP model. However, the input component recorded a lower score (2.8), indicating limitations in professional staffing, infrastructure, and institutional support. The process component also showed a moderate score (3.2), revealing that the program remains largely reactive and lacks optimal implementation of preventive strategies such as classroom guidance. The study concludes that while the GC program demonstrates moderate effectiveness, it requires further improvement in strategic planning, digital documentation, and long-term evaluation practices. Recommendations include developing a more comprehensive evaluation instrument and strengthening preventive services that are responsive to students' evolving needs.